DC power supply system based on parallel battery modules and its HMI display - Jiao, Yuting (Nanyang Technological University, 2022)
As a core part in DC power systems such as substations and power plants, batteries directly determine the reliability and provide safe operation for the DC power supply system. In traditional DC power systems, multiple batteries are normally connected in series to form a battery bank, which create some problems that are usually solved by using parallel battery modules. Despite being effective, this solution normally brings some problems. To address these challenges brought by using individual batteries in series, this dissertation adopts a DC power supply system with parallel battery modules, and the outline of this dissertation is as follows. Firstly, the operation mechanism and corresponding advantages of the system are introduced, and then the requirements and functional analysis of the DC power supply monitoring device are explained. The DC power supply based on parallel battery modules is a significant change from the traditional series connection approach in terms of design organisation, management and monitoring. Therefore, a corresponding DC power supply monitoring device is developed for this parallel battery structure DC power supply system. The communication software is designed using the Qt interface in C++ and incorporates object-oriented design features. The software platform applies an embedded Linux operating system based on the ARM architecture with high real-time performance. The human-machine interaction function of the designed integrated power supply monitoring device performs information visualisation and it can display various system operation status and alarm information, as well as parameter settings and manual control. The device has a simple interface, which is practical and user-friendly, whereby users can quickly grasp the operation of the system. System faults can also be detected and then fixed in time.